(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: In Iraq their are accumulating long-stay patients in the only mental hospital in the absence of community based-care health services. This paper suggests the first step toward deinstitution-alization. Objectives: The Study aimed to identify the prevalence of the Long-Stay inpatients that can live in alternative accommodation to mental hospital. Methods: A random sample of 100 male patients admitted to AL-Rashad hospital for 2 years and over were studied. The required information were obtained from; case notes, opinion of treating psychiatrists, nursing staff and social workers. The patients and some of their families were interviewed in semi-structured form General physical examination of the patients was carried out. Results: The mean duration’s of illness and of admission were 19.3 and 7.7 years respectively. The patients who were able to live outside the hospital were 46% of the sample. The appropriate homes for them included: supervised homes by hospital staff (N=10), less supervised homes (N=16) and community based homes (N=20). Although 77 patients had families, 78% of them rejected their patients. Conclusion: The implications of the results suggest focussing on the community care of the mentally ill. A co-ordination between the health and social authorities is recommended for humanistic and cost benefits reasons. Key words: Chronic Mentally Ill, Community Care, Schizophrenia in Iraq, Community Psychiarty, Mental Hospitals in Developing Countries.